Innovative Learning Approaches: Quantum Chemistry Board Games for Education and Computational Thinking Strategies - Ilmiyati, Dian; Risky, Elsyafahriza; Chaeruman, Uwes Anis; Paristiowati, Maria; Istianah, Istianah (Jurnal Tadris Kimiya, 2024)
Computational thinking (CT) learning is becoming increasingly important in today's education in developing critical thinking and problem-solving skills. The development of board games is one of the techniques used to hone problem-solving skills by integrating CT into the learning process. Through this innovative learning approach, abstract concepts in atomic structure and the periodic system of elements are integrated into components of the game. The research aims to improve students' critical thinking and problem-solving skills in challenging chemistry content such as quantum numbers. This research includes the design, development, and implementation stages of board games in learning. The N-gain score of 0.7 is achieved, indicating an improvement in the effectiveness of learning chemistry subjects on atomic structure and the periodic system of elements through the designed board games. In addition, students provide positive feedback regarding engagement and interest in learning through this interactive approach. These results indicate that the use of CT-integrated board games can be an effective tool for teaching chemistry materials at the high school level while promoting students' CT skills. Well-designed board games can be used as effective learning tools to improve student's critical thinking and problem-solving skills in quantum numbers.